IMPLEMENTASI PENDIDIKAN INKLUSI MELALUI PENYELENGGARAAN DAN STRATEGI PEMBELAJARAN DI SLB INSAN TIARA BANGSA - Ika Ratnaningrum; Syifa Nur Saadah; Andika Budi Raharjo; Deswa Havid Fernando (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of inclusive education at SLB Insan Tiara Bangsa, focusing on teaching strategies, applied policies, and challenges encountered. This qualitative research employed observation, interviews, and documentation techniques, specifically in the class for students with intellectual disabilities at the elementary level. The results show that the school implements inclusive education through inclusive vision and mission statements, the use of the Merdeka Curriculum, and tailored teaching strategies based on students’ needs. Various services are provided, including visual media, behavior therapy, selfdevelopment activities, and Pancasila Student Profile projects. Teachers play a key role in designing individualized learning and conducting regular evaluations. However, challenges remain, such as limited disability-friendly infrastructure and the need for further teacher training. This study highlights the importance of collaboration among schools, teachers, parents, and communities in supporting effective and sustainable inclusive education.